The Role of MBKM Policy in Enhancing Higher Education Quality in Indonesia - Saa, Septinus (Side: Scientific Development Journal, 2025)
This study explores the role of the Merdeka Belajar Kampus Merdeka (MBKM) policy in enhancing the quality of higher education in Indonesia. The primary objective is to evaluate the impact of MBKM on student learning outcomes, university-industry collaboration, and the overall effectiveness of higher education institutions in meeting the demands of the labor market. The research adopts a qualitative approach through a literature review, analyzing various academic journals, government reports, and case studies related to MBKM's implementation from 2017 to 2022. Data were systematically collected from reliable sources, and thematic analysis was used to identify key trends and patterns related to MBKM’s effects on educational quality. The study finds that MBKM significantly improves student engagement, employability, and the relevance of academic programs by facilitating practical learning experiences such as internships and research projects. The policy has also fostered stronger university-industry partnerships, enhancing student access to industry insights and career opportunities. However, challenges such as curriculum adaptation, resource disparities, and faculty resistance hinder its full implementation, particularly in rural and under-resourced universities. In conclusion, MBKM has made a positive contribution to the quality of higher education in Indonesia, but further efforts are needed to address implementation barriers. The findings suggest that a targeted approach to resource distribution and faculty training is essential for maximizing the policy's potential. Future research should focus on assessing the long-term effects of MBKM on graduate success and institutional development, ensuring that all students benefit equally from the policy.